Thrombin - Fibrinogen Clotting Times - Waugh, D. F; Baughman, D Joe; Juvkam-Wold, Constance (Thrombosis and Haemostasis, 1968)
The fundamental variation to be taken into consideration in comparing clotting time averages is that of the clotting time assay itself. A variation is ετ whose true variance is στ2 and the experimental estimate of this variance sτ2. Described is a clotting time machine automated with respect to temperature, thrombin volume, thrombin injection, stirring and time determination so that the only subjective observation is that of the clotting time endpoint. Statistical analysis of sτ2 has been made using protocols in which measurements either were carried out in a particular time sequence (regression type protocol) or were randomized (randomization type). An experimental unit is a dilute thrombin solution, a dilute fibrinogen solution and an operator-machine. The dilute reagents come from stock reagents. Characteristics of the system are as follows. 1. For a wide variety of experimental units the ετ are time independent and normally distributed. The sτ2 from single lots of stock reagents appear to be estimates of the same στ2. If different stock reagents are used the measured sτ2 show that στ2 may change significantly. 2. The variance increases with the clotting time. An approximate square relationship has been used for normalization. 3. The operator-machine and dilute solutions of stock thrombin appear to be remarkably uniform. 4. A change in στ2 between experimental units is due to fibrinogen and appears particularly when different lots of fibrinogen, Armour’s Fraction I, are used to prepare the purified stock reagent. 5. When time dependent changes occur in experimental units, they are also most likely due to fibrinogen instability. When the storage temperature of stock-F is decreased from —20° to —95°, fibrinogen solubility is stabilized and regression decreased. 6. When instabilities can be made small, a randomization type protocol is preferred since fewer clotting times are required to characterize an experimental unit. When instability is important, a number of assays must be invested in its detection. This number increases approximately linearly with sτ2 and decreases linearly as the time period for assays increases. The most important limitation to the examination of regressions is the number of clotting times an observer can perform on a single day.